Purchase decision: The role of brand image, product quality, and price - Gatri, Betasari Ulfa; Waeno, Mahamadaree (Journal of Management and Business Insight, 2025)
Purpose-Changes in consumer preferences from simply considering price to paying attention to quality, brand image, and product perception have become an important concern for companies, especially in the beauty industry. In this context, body lotion is one product that consumers consider not only based on price but also quality and brand image. Based on this, this study aims to analyze the influence of brand image, product quality, and price on the purchase decision of Marina body lotion in the Yogyakarta, Indonesia. Design/Methodology/Approach- This study analyzes the factors that influence the decision to purchase Marina brand body lotion products. The sampling technique used was purposive sampling and having purchased Marina products. The number of respondents in this study was 105 people, with data collection using an online questionnaire. The data were analyzed using multiple linear regression with the help of SPSS software version 25. Findings-The results show that brand image, product quality, and price have a positive and significant effect on purchasing decisions. Among the three, product quality has the most dominant effect on consumer purchasing decisions regarding Marina body lotion. Research limitations/implications-The limitations of this study lie in the limited number of samples and their uneven distribution, as they are dominated by certain areas in Yogyakarta, Indonesia. In addition, the research objects are limited to Marina brand body lotion products, so the results cannot be generalized to similar products or other brands. Originality/value-This study focuses on one brand of lotion (Marina) and one region (Yogyakarta, Indonesia). This study has not been conducted before, making it interesting for further research.